A stretchable fiber nanogenerator for versatile mechanical energy harvesting and self-powered full-range personal healthcare monitoring. (November 2017) - Cheng, Yin; Lu, Xin; Hoe Chan, Kwok; Wang, Ranran; Cao, Zherui; Sun, Jing; Wei Ho, Ghim
Abstract: Wearable electronics have gained dramatic development in recent years, owing to the advancement in flexible/stretchable electronics, and achieved considerable progress in various applications. Nanogenerators capable of harvesting energy from human activities is considered as a promising alternative for powering the wearable electronic devices, considering the sustainability and rich biomechanical energy from human body. Currently, most of the nanogenerators are aimed at converting limited forms of mechanical energy, mostly pressing or bending, which hampers adaptive exploitation of bodily energy source. Also, the incapability to respond to multiple forms of mechanical stimuli deters the nanogenerators from functioning as full-range human activities sensors. Here, we devise a stretchable integrated nanogenerator-sensory coaxial core-sheath fiber with improved functionality and sustainability. The combination of materials engineering and structure design enables the fiber to scavenge versatile mechanical energy, including stretch, bend, twist and press, through a gap size variation induced electrostatic effect. Besides, the fiber realizes the detection of joint-bending and joint-twisting related motions, such as walking and elbow rotation, and also succeeds in capturing subtle physiological signals, such as breath, pulse and speech recognition, which paves the way for full-range personal healthcare monitoring and documenting in a self-powered, wearable and noninvasive manner. Graphical abstract: A stretchable nanogenerator with coaxial core-sheath fiber architecture is devised to enable harvesting of versatile mechanical energy, including stretch, bend, twist, and press. This fiber nanogenerator also realizes the detection of full-range human activities, ranging from rigorous motions to subtle physiological signals, in a self-powered, wearable and noninvasive manner, paving the way for personal healthcare monitoring. Highlights: A stretchable and wearable fiber nanogenerator (FNG) with coaxial core-sheath architecture was devised and fabricated. The FNG can harvest versatile mechanical energy, based on a gap size variation induced electrostatic effect. The FNG is utilized as a self-powered, wearable sensor that realizes the full-range personal healthcare monitoring.